Cyberloafing behavior on employee performance - Farid, Farid; Akkas, Nasrulhak; Mande, Henni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
In the study of employee performance management, this is an issue that requires important attention, where the performance of individual employees in the organization is part of organizational performance and can determine organizational performance. The increasing use of the internet among employees in various companies and agencies in Indonesia will certainly affect employee performance, both positively and negatively. This study aims to determine the effect of browsing and e-mail on employee work productivity at the Plantation and Animal Husbandry Service of Central Sulawesi Province. This study used a sample of 73 respondents and quantitative research type. Data collection techniques using questionnaires. Data analysis techniques using multiple linear regression tests. The results showed that variables browsing activities (X1) do not have a significant effect on employee performance and activity of sending emails (X2) has a positive effect on employee performance. If these two activities are examined simultaneously, it turns out that they have a significant effect on employee performance.